2021
DOI: 10.3389/fcell.2021.761273
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions and Therapeutic Potential of Autophagy in Spinal Cord Injury

Abstract: Autophagy is an evolutionarily conserved lysosomal degradation pathway that maintains metabolism and homeostasis by eliminating protein aggregates and damaged organelles. Many studies have reported that autophagy plays an important role in spinal cord injury (SCI). However, the spatiotemporal patterns of autophagy activation after traumatic SCI are contradictory. Most studies show that the activation of autophagy and inhibition of apoptosis have neuroprotective effects on traumatic SCI. However, reports demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 151 publications
0
17
0
Order By: Relevance
“…Autophagy, a lysosome-based degradation process, is evolutionarily conserved and plays a critical role in diverse pathophysiological conditions across various environments. (Liao et al, 2021). Necroptosis is a regulated form of necrosis mediated by RIPK1 and RIPK3 that is capable of exacerbating cell death and neuroinflammation in the pathogenesis of central nervous system diseases (Fan et al, 2019;Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, a lysosome-based degradation process, is evolutionarily conserved and plays a critical role in diverse pathophysiological conditions across various environments. (Liao et al, 2021). Necroptosis is a regulated form of necrosis mediated by RIPK1 and RIPK3 that is capable of exacerbating cell death and neuroinflammation in the pathogenesis of central nervous system diseases (Fan et al, 2019;Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[ 76 ] Moreover, study of Li et al indicate that treatment with oxymatrine of rats with spinal cord injuriessignificantly ameliorates apoptosis and regulates autophagy, which aremediated by activation of the AMPK/SIRT1 signaling pathway. [ 77 ] Additionally, findings of numerous research studies have indicated that oxymatrine can increase the expression of AMPK, and it is well known to regulatemetabolism, oxidative stress, inflammation, and apoptosis in diabetic conditions, which may attenuate, and could play a promising role in the complications of hyperglycemia‐induced ventricular hypertrophy, cardiac fibrosis, contractile dysfunction, and heart failure.…”
Section: Involvement Of Various Cellular Pathways In Dcmmentioning
confidence: 99%
“…Lithium has been shown to inhibit multiple phosphomonoesterases being structurally similar to magnesium [ 89 ]. Lithium can improve the microenvironment in the spinal cord and promote the regeneration and survival of motor neurons [ 90 ]. Lithium chloride can boost the secretion of brain-derived neurotrophic factor (BDNF) in the axons of motor neurons following spinal cord injury [ 91 , 92 ].…”
Section: Lithium and Cellular Biology Of Scimentioning
confidence: 99%